Cyber Insurance Adoption and Digitalisation in Small and Medium-Sized Enterprises - Nazim Taskin; Aslı Özkeleş Yıldırım; Handan Derya Ercan; Martin Wynn; Bilgin Metin (Information)
Digitalisation has significantly increased cybersecurity risks in organisations, notably for small to medium-sized enterprises (SMEs), in which IT departments often have relatively small teams and limited resources. Cyber insurance enables SMEs to navigate cybersecurity risks more economically, providing an essential risk transfer alternative to costly reduction strategies. This article examines the antecedents, emergence, and application of cyber insurance as a solution to cybersecurity concerns against the backdrop of increasing digitalisation. The research adopts a quantitative deductive approach, with an analysis of relevant literature providing the basis for the development of 12 hypotheses, which are then tested via a survey of 168 SMEs in Turkey. Using the Technology–Organisation–Environment–Individual (TOE-I) model as a top-line conceptual framework, the article finds that cyber insurance policy adoption has facilitated a more rapid and secure digitalisation process and that the mitigation of financial risk associated with cyberattacks has allowed companies to invest more widely in information technologies and systems. The article clearly has its limitations, in that it is based on primary research in one European country, but the authors believe that it nevertheless provides some new insights into the potential benefits of cyber insurance, and the key issues SMEs must consider when considering adopting a cyber insurance policy. The findings will be of practical relevance to SMEs and other organisations reviewing their cybersecurity strategy and are also of relevance to the wider debate around the costs and benefits of digitalisation.